Pengaruh Motivasi Belanja Hedonis Terhadap Pembelian Impulsif Di E-Commerce Shopee Pada Generasi Milenial - Abdurachman, Aditia; Arifah, Alfin Nur; Lestari, Dheri Febiyani; Ridwan, Rizky (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This study aims to understand the impact of Hedonic Shopping Motivation on impulsive buying behavior among Millennial users of Shopee e-commerce. A quantitative approach was utilized in this research, with a questionnaire as the data collection tool. The sample consisted of 172 respondents who are Shopee e-commerce users. The results indicated that Hedonic Shopping Motivation has a significant influence on impulsive buying behavior among Millennial Shopee users, with a t-significance value of 0.000 < 0.05. This demonstrates a significant relationship between Hedonic Shopping Motivation and impulsive buying behavior on Shopee among Millennials. The study also found a correlation of 0.540 between the independent and dependent variables, indicating a strong relationship between these variables. The coefficient of determination shows that 29.16% of the variation in impulsive buying behavior can be explained by the Hedonic Shopping Motivation variable, while the remaining portion is due to other factors not addressed in this study. Keywords: Hedonic Shopping Motivation, Impulsive Buying